Lectotypifications in Orthoclada (Poaceae, Panicoideae, Zeugiteae) - Dórea, Marcos Da Costa; de Oliveira, Reyjane Patricia; Welker, Cassiano Aimberê Dorneles (Phytotaxa, 2016)
The grass genus Orthoclada Beauvois (1812: 69) is currently placed in the subfamily Panicoideae, tribe Zeugiteae (Soreng et al. 2015), and includes only two species from forests of Tropical America and Africa: O. laxa (Richard 1792: 106) Beauvois (1812: 70) and O. africana Hubbard (1940: 3419) (Kellogg 2015, The Plant List 2016). The genus was formerly included in subfamily Centothecoideae (Clayton & Renvoize 1986), which was recently submerged into the Panicoideae (Sánchez-Ken & Clark 2010, Soreng et al. 2015). Orthoclada is characterized by its bisexual flowers and the unusual fusion of its rachilla internode to the palea keels (Kellogg 2015).